THE LEVEL OF UNDERSTANDING OF THE POHSANTEN VILLAGE TOURISM DEVELOPMENT TEAM ON COMMUNITY-BASED TOURISM - Ni Made Ernawati (P3M Politeknik Negeri Bali, 2018)
Community-based tourism (CBT) is used as a catalyst for village development in Indonesia. However, people who wish to develop CBT experience many obstacles in carrying out the development. These constraints ranging from capital, to the limited competency of human resources supporting tourism. In developing tourism, communities need to understand the characteristics of CBT and know activities need to be carried out for the development project. Considering the situation faced by the village, a community service was conducted in Pohsanten Village Jembrana District Bali Province, to assist the community to prepare the implementation of CBT development. Pohsanten is rich with tourist attractions ranging from natural to cultural in the form of waterfalls, rural culture and art, cacao farming as well as spiritual tourism highlighting Pasatan Temple. To develop the understanding of the community members, especially the Pohsanten Village CBT Development Team, several activities have been conducted, these such as: CBT dissemination, field observation in the village, a comparative study to CBT areas in Bali, and participating in a cooking class i.e. preparing breakfast for guest. After the activities took place, a measurement of the level of understanding of the Pohsanten Village CBT Development Team was carried out to know their level of understanding of the CBT concept. The results show that the Team has a good understanding of CBT; therefore, it could be concluded that the method is effective in establishing an understanding toward CBT. It is expected that with a substantial understanding the Team can better develop the tourism project in Pohsanten; considering that, this stage is the beginning and a critical phase of the village tourism development. There are still much more activities that need to be undertaken in developing the Pohsanten CBT that is professionally and independently organized and operated.